Data from Campagna et al 2013 Ecology and Evolution - Campagna, Leonardo; Van Coeverden De Groot, Peter J.; Saunders, Brenda L.; Atkinson, Stephen N.; Weber, Diana S.; Dyck, Markus G.; Boag, Peter T.; Lougheed, Stephen C. (Dryad Digital Repository, 2013)
Microsatellite data set and all Structure, Geneland, Arlequin and IMa2 input files.